Experimental Analysis of Mechanical and Thermal Properties of Sugar Palm Fiber-Plastic Composite Roofs - Wijianto, Agus; Ma'a, Mustaza; Yanda Zaira, Jupri; Rizkyana, Rizkyana; Arif Sitinjak, Bherry (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
This research aims to enhance the performance of Palm Sugar Fiber (PSF) or Ijuk roofing by combining it with recycled High Density Polyethylene (HDPE) plastic as a binder and outer protective layer. The method was used an experimental study with several variations in fiber form and mass, followed by performance testing on temperature, noise, and mechanical properties (tensile, compressive, and impact strength). The results showed that the 40-gram long fiber variation provided the most optimal performance. The indoor temperature beneath the PSF roof was recorded at 38.2°C. The absolute thermal conductivity value was calculated at 0.23 W/m·K. In noise reduction tests, the PSF roof recorded 39.6 dB compared to 74.2 dB for zinc roofing. In terms of strength, the palm fiber roof achieved a tensile strength of 13.24 MPa and the impact strength of 3.16 Joules. Thus, the fiber (fiber) composite roof with HDPE binder demonstrates superior thermal and sound insulation capabilities, as well as sufficient mechanical strength, making it a promising environmentally friendly alternative for modern roofing materials.